2007
DOI: 10.1071/sh06045
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health of homeless youth: prevalence and correlates of sexually transmissible infections

Abstract: Background: The study examined risk factors for having ever contracted sexually transmissible infections (STI) among a high-risk sample in midwestern USA. Methods: A cross sectional survey was conducted among 428 homeless youth aged 16–19 years. Assessed correlates included child maltreatment, street exposure, sexual histories, street experiences and substance use. Results: Multivariate analyses revealed that males were 86% less likely to have had STI compared with females (adjusted odds ratio [AOR] = 0.14; 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…The most common interests in mHealth programs relating to HIV/STIs, reproductive health, and mental health revealed an urgent need to utilize mHealth strategies in these areas. This is important, as studies have shown that youth experiencing homelessness have disproportionately high rates of mental illness, HIV, and other STIs compared to non-homeless youth and face barriers to accessing health information and services (Marshall et al, 2009;Tyler et al, 2007;Whitbeck et al, 1999). An mHealth platform could be utilized to facilitate access for homeless youth to HIV/STI combination prevention methods (Catalani, Philbrick, Fraser, Mechael, & Israelski, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The most common interests in mHealth programs relating to HIV/STIs, reproductive health, and mental health revealed an urgent need to utilize mHealth strategies in these areas. This is important, as studies have shown that youth experiencing homelessness have disproportionately high rates of mental illness, HIV, and other STIs compared to non-homeless youth and face barriers to accessing health information and services (Marshall et al, 2009;Tyler et al, 2007;Whitbeck et al, 1999). An mHealth platform could be utilized to facilitate access for homeless youth to HIV/STI combination prevention methods (Catalani, Philbrick, Fraser, Mechael, & Israelski, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Other scholars point to the reinforcing nature of the relationship between substance use and sex trading (see 23,24 ). Specifically, Tyler et al 25 argue that pressure to pay for drugs may push one to trade sex for money or that drug use may heighten the tendency to engage in the behavior. Evidence also suggests that youth who have ever tried alcohol, marijuana, or other drugs have also traded sex for these substances.…”
Section: Literature Review Demographic Characteristics and Trading Sexmentioning
confidence: 99%
“…National estimates suggest that nearly 2 million youth experience homelessness each year [1-3], and there is a large body of research demonstrating the increased health risks associated with homelessness for these youth [4-6]. Research suggests that pet ownership in the general population may confer a wide range of benefits for health and well-being [7-12].…”
Section: Summary Introductionmentioning
confidence: 99%